Consumers' perceptions and responses towards online retailers' CSR. Issue 12 (11th July 2020) - Dang, Van Thac; Nguyen, Ninh; Wang, Jianming
Abstract : Purpose: Anchored on social trust theory, social identity theory and signalling theory, this study investigates the process of how consumers respond to online retailers' corporate social responsibility (CSR). Design/methodology/approach: Following the hypo-deductive research design, a unique model was developed to link online retailers' CSR with consumer purchase intention through brand identification and word of mouth (WOM). This model was subsequently tested and validated by conducting an online survey to 239 customers of a major online retailer in China, that is, JD.com. Findings: Analysis using structural equation modelling demonstrates that online retailers' CSR is positively associated with consumer purchase intention, and brand identification positively mediates such an association. In addition, WOM exhibits a mediating effect on the relationship between perceived online retailers' CSR and consumer purchase intention and between brand identification and consumer purchase intention. Practical implications: Online retailers must endeavour to employ CSR as a strategy to enhance consumer purchase intention and behaviour. Moreover, they should develop communication programmes that highlight their engagement in CSR activities to improve their brand image and facilitate consumers' positive WOM. Originality/value: To the best of the researchers' knowledge, this study is the first to examine the mediating roles of brand identification and WOM in the relationship between online retailers' CSR and customer purchase intention. Furthermore, this study extends current knowledge about online retailers' CSR and its potential impact in emerging economies by focussing on the context of China.